Dynamics of Capital Structure, Risk-Taking Behavior, and Profitability across the Vietnamese Banking System: Evidence from a Panel Vector Autoregression - PHAM, Minh Phu; HOANG, Cuong Van; TRAN, Chung Kim; VU, Hung Van; LE, Nga Thuy Thi; NGUYEN, Bo Cong (Journal of Advanced Research in Law and Economics; Vol 10 No 8 (2019): JARLE Volume X Issue 8(46) Winter 2019, 2019)
The paper examines the interdependence between the profitability, risk-taking behavior, and capital structure across the Vietnamese banking sector, using panel vector autoregression with quarterly data of the 22 banks over 2014Q1–2019Q3. The outcomes indicate profit or solvency shock increases leverage, while the profit and solvency respond negatively to the leverage shock and their movement over time path is pretty similar. This reflects that the insolvency risk is sensitive to the wellbeing volatility due to the weak capital. Moreover, the forecast variance in the leverage is mainly predicted by the profitability shock, while that of solvency is by the leverage one. The estimated variance in prosperity is mainly explained by the inefficiency shock. Thus, regarding policy recommendations, in the long run, Vietnamese financial regulators need to be continuously consistent with capital strength-supporting policies. However, other policies facilitating an effective financial environment are also simultaneously established to help banks minimize operating costs for higher management efficiency and thereby profitability. This supports the banks to partially offset the negative impact of increased capital which might reduce their profitability. Finally, strengthened supervision policies are also necessary, especially when the banks are more profitable because they intentionally relax borrowing and leverage restrictions.